Two new species in the Anthaxia (Anthaxia) candens (Panzer, 1793) species-group from Iran and Turkey, with taxonomic notes on the group (Coleoptera: Buprestidae) - Bílý, Svatopluk (Zootaxa, 2006)
Two new species in the Anthaxia (Anthaxia) candens (Panzer, 1793) species-group: Anthaxia (Anthaxia) jenisi new species, from southern Iran and A. (A.) pyrosoma new species, from eastern Turkey, are described, illustrated and compared with related species. Anthaxia urens Abeille de Perrin, 1882 is removed from synonymy with A. lucens Küster, 1852 and is treated as a wellcharacterized subspecies. A key to the species of the A. candens species-group is provided and short comments on the taxonomic history, distribution and bionomy of the group are given